Influence of Kα absorption in (111) Ge crystal on spectral yield of parametric X-rays; Physics Letters A; Vol. 147, iss. 5-6 - Adishchev Yu. N. Yuri Nikolaevich; Kaplin V. V. Valery Viktorovich; Potylitsyn A. P. Alexander Petrovich; Uglov S. R. Sergey Romanovich; Vorobiev S. A. Sergey Aleksandrovich; Babadzhanov R. D.; Verzilov V. A. (1990, 1990)
Title screen